Male breast cancer (MBC) – a review - Salati, Sajad Ahmad; Naqash, Mohd Mubarik; Kadi, Azzam Al (International Journal of Health Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> About 1% of all breast cancers occur in males. The disease has shown increasing incidence in recent decades with the aging of global populace. Due to small size of breasts in male, the disease is easier to detect, yet the lack of awareness about this disease results in late reporting of patients. This article reviews the various aspects associated with the male breast cancer (MBC). <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->